A Facile Approach to Covalently Functionalized Graphene Nanosheet Hybrids and Polymer Nanocomposites. Issue 8 (31st May 2016) - Fu, Jifang; Zong, Peisong; Chen, Liya; Dong, Xing; Shang, Dapeng; Yu, Wenqi; Shi, Liyi; Deng, Wei
Abstract: Homogeneous dispersion and a good interface between polymer and filler is crucial to obtain high‐performance polymer composites. In this work, we use a novel method employing organic aminopropyl‐functionalized nanosilica sols (OAS‐sols) to functionalize graphene oxide (GO) and thereby synthesize OAS covalently grafted graphene hybrid nanosheets (OAS‐graphene). The spherical OAS covalently attached on the two‐dimensional (2D) nanosheet GO surfaces creates OAS‐graphene hybrids, which have large surface areas and homogeneous amino active sites distributed on the nanosheets. The OAS‐graphene gave an improved dispersion and interface compatibility as well as a decreased thermal interfacial resistance. As a result, the thermal conductivity and mechanical properties of the epoxy nanocomposites were significantly improved at low loading while maintaining high electrical insulative properties. Abstract : At the interface : A facile and cost‐effective method is demonstrated to improve graphene oxide (GO) dispersion and interface quality in an epoxy matrix by simultaneously functionalizing and reducing GO by covalently grafting organic aminopropyl‐functionalized nanosilica sols (OAS). The covalent functionalization of GO with OAS makes the hydrophilic GO become hydrophobic and provides the active sites that allow linking between the graphene‐based sheets and the epoxy matrix, which ensures improved thermal conductivity and mechanical properties.